The ATM Forum developing implementation agreements. - Dobrowski, G.H.
ATM technology is playing an important role in providing multiservice infrastructure and its support of multimedia communications. This article describes the ATM Forum, and its successful collaborative efforts to bring the data, private, and public networking cultures together for world-class solutions. Key achievements toward the deployment of the global information infrastructure are described
Keywords: ATM Forum; Data networking; Global information infrastructure; Implementation agreements; Multimedia communications; Multiservice infrastructure; Private networking; Public networking